Brakes (Professional truck technician training series)
This course offers more than 8.5 hours worth of technical instruction for automotive technicians and individuals interested in becoming a brakes specialist. From hydraulic systems to collision warning systems, medium/ heavy duty truck technicians can get all the need-to-know information with this highly interactive, innovative e-learning tool.